Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Pelanggan Pt.Telkom (Persero) Gunungsitoli (Jurnal Ilmu Sosial Dan Politik, 2025)
Customer satisfaction is one of the important indicators in determining the success and sustainability of a company, especially in the telecommunications service sector, which is highly competitive. PT. Telkom (Persero) Gunungsitoli, as an internet service provider, faces the challenge of a mismatch between customer expectations of fast and stable network quality and the reality of services that still experience disruptions. This study aims to analyze the factors that influence customer satisfaction, including service quality, price, network stability, and customer service. This study uses a qualitative approach with a descriptive design. Primary data was obtained through in-depth interviews with active customers of PT. Telkom Gunungsitoli who have been subscribing for at least six months, and was supported by key informants from within the company. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that service quality, especially in terms of responsiveness, friendliness, and professionalism of staff, is a major factor affecting customer satisfaction. Good network stability is also considered very important, although there are still complaints about connection disruptions. The price factor is considered relatively higher than other providers, but is considered commensurate with the benefits received. In addition, prompt customer service in responding to complaints contributes significantly to building user trust and loyalty. In conclusion, customer satisfaction with PT. Telkom Gunungsitoli is influenced by a combination of technical and non-technical qualities. The company needs to strengthen its network quality, improve customer service competencies, and pursue continuous innovation in order to maintain customer loyalty and increase competitiveness in the market.